Development of a new visible spectrophotometric method for the analysis of Ganciclovir in bulk sample and dosage form. (2015)
Purpose: To develop and validate a simple visible spectrophotometric method for the quantitative determination of ganciclovir in bulk sample and dosage form. Method: The method was based on the diazo coupling reaction between diazotized ganciclovir and acidified p-dimethylaminobenzaldehyde. Various analytical parameters for the azo adduct were established. Validation of the new method was carried out using current ICH guidelines with parameters including linearity, repeatability, reproducibility and selectivity determined. The developed method was thereafter applied to determine ganciclovir in a commonly available brand. Results: Coupling reaction generated a yellow-coloured product in an alcohol medium with optimal wavelength at 404 nm. Linear correlation was obtained at concentrations of 10.3 - 25.7 μg/mL. The method was accurate and precise with recovery in the range of 99.37 - 103.15 % while intra- and inter-day precision (% RSD) at three different concentrations was < 2.7 %. The limits of detection and quantification were 0.23 and 0.70 μg/mL, respectively. When applied to the analysis of the dosage form, there was no statistically significant difference between the new method and the official HPLC method. Conclusion: The method is simple, inexpensive, reproducible and fast, and can be employed as a reliable alternative to the official method for the routine analysis of ganciclovir in bulk and dosage forms.